Akar Pluralisme dalam Pendidikan Muhammadiyah - ABDUL MU’TI (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2016)
This paper discusses the nature of Muhammadiyah educational institutions and relates it to the diverse socio-religious background of Indonesian society. Renowned as the largest modernist Islamic movement in Indonesia and Southeast Asia, which promotes the purity of Islam, Muhammadiyah in fact has been faced with notions of religious and cultural pluralism, and therefore, it has to seeks ways of how to formulate Islam in plural society. This article is a theoretical exposition of Muham- madiyah and its encounters with religious pluralism, and how Muhammadiyah translates notions of pluralism into praxis in its educational institutions. This paper argues that educational institutions of Muhammadiyah have widened path for deepening inter-religious dialogue and interaction in the diversity of Indoensian society.